2011
DOI: 10.1242/dev.73874
|View full text |Cite
|
Sign up to set email alerts
|

SPOC1 (PHF13) is required for spermatogonial stem cell differentiation and sustained spermatogenesis

Abstract: Summary SPOC1 (PHF13) is a recently identified protein that has been shown to dynamically associate with somatic chromatin, to modulate chromatin compaction and to be important for proper cell division. Here, we report on the expression of SPOC1 in promyelocytic leukaemia zinc finger (PLZF)-positive undifferentiated spermatogonial stem cells (SSCs) of the mouse testis. To investigate further the biological function of SPOC1 in germ cells we generated Spoc1 mutant mice from a gene-trap embryonic stem cell clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…PLZF, also known as ZBTB16 (Zinc Finger And BTB Domain Containing 16) is a consensus marker for undifferentiated spermatogonia (20). Immunocytochemistry analysis illustrated the expression of this factor in the colonies derived from the cultured cell suspensions (Fig.…”
Section: Characterization Of Sscsmentioning
confidence: 99%
“…PLZF, also known as ZBTB16 (Zinc Finger And BTB Domain Containing 16) is a consensus marker for undifferentiated spermatogonia (20). Immunocytochemistry analysis illustrated the expression of this factor in the colonies derived from the cultured cell suspensions (Fig.…”
Section: Characterization Of Sscsmentioning
confidence: 99%
“…Yang et al found that 2410076121rik and other new genes were specifically expressed in SSCs in mouse via transcriptome sequencing, most of them are played important role in maintaining the proliferation and differentiation of SSCs . van Bragt et al and Bördlein et al demonstrated that knocking out SPOCl led to the apoptosis of SSC and blocked the formation of spermatogonia …”
Section: Introductionmentioning
confidence: 99%
“…8 van Bragt et al and Bördlein et al demonstrated that knocking out SPOCl led to the apoptosis of SSC and blocked the formation of spermatogonia. 9,10 Previously, we have studied the molecular mechanism of male germ cells in chickens. The three types of cells, such as ESCs, primordial germ cells (PGCs), and spermatogonial stem cells (SSCs) on the time axis of germ cell development and differentiation were analyzed through transcriptome sequencing.…”
Section: Introductionmentioning
confidence: 99%